The legacy of sovereign joy God's triumphant grace in the lives of Augustine, Luther and Calvin - Piper, John, 1946- (Wheaton, IL Crossway, 2000)
Includes bibliographical references and indexes.
Keywords: Augustine, Saint, Bishop of Hippo; Luther, Martin, 1483-1546.; Calvin, Jean, 1509-1564.